The quantification of sodium intake from discretionary salt intake in New Zealand using the lithium-tagged salt method - Wang, Nan Xin; McLean, Rachael M.; Cameron, Claire; Skeaff, Sheila A. (Frontiers in Nutrition, 2023)
Introduction: Discretionary salt (added in cooking at home or at the table) is a source of sodium and iodine in New Zealand (NZ). The amount of discretionary salt consumed in a population has implications on policies regarding sodium and iodine. Sodium intake from discretionary salt has not been quantified in NZ. The aim of this study was to estimate the proportion of total sodium that comes from discretionary salt in adults using the lithium-tagged salt method. Method: 116 healthy adults, who regularly consume home-cooked meals and use salt during cooking or at the table, aged 18-40 years from Dunedin NZ were recruited into the study, which took place over nine days. On Day 1, participants were asked to collect a baseline 24-hour urine to establish their normal lithium output. From Day 2-Day 8, usual discretionary salt was replaced with lithium-tagged salt. Between Day 6 and Day 8, participants collected another two 24-hour urines. A 24-hour dietary recall was conducted to coincide with each of the final two 24-hour urine collections. Urinary sodium was analysed by Ion‑Selective Electrode and urinary lithium and urinary iodine were analysed using ICP-MS. 24-hour dietary recall data was entered into Xyris FoodWorks 10. Results: 109 participants with complete 24-hour urine samples were included in the analysis. From the 24-hour urine collections, the median urinary excretion of sodium and iodine was 3222 mg/24hr (25th, 75th percentile: 2516, 3969) and 112 µg/24 hours (82, 134). The median estimated sodium intake from discretionary salt was 13% (25th, 75th percentile: 7, 22) of the total sodium intake or 366 mg/24hr (25th, 75th percentile: 186, 705). Conclusion: The total sodium intake was higher than the suggested dietary target of 2000 mg/day. In this sample of healthy adults 18 to 40 years old, 13% of total sodium intake derived from discretionary salt. Discretionary salt is an additional source of iodine if iodised salt is used. Policies to reduce sodium intake is recommended to include a range of strategies to target discretionary and non-discretionary sources of salt and will need to take into account the contribution of iodine from discretionary salt intake.